Municipal solid wastes an overview of plastic waste management system / Ahmad Faisal Alias ... [et al.] - Alias, Ahmad Faisal; Ali, Nor Eeda; Teriman, Suharto; Talmizi, Nurain Mohd (2021)
Plastic waste comprises of a quarter of total municipal waste generation including in Malaysia. This type of waste generation increases annually and is largely fuelled by rapid urbanisation and industrialisation, population increase and shifts in lifestyle as well as changes in patterns of consumerism. These phenomena have created significant pressures on local governments especially local authorities who have to fork out nearly half of their annual expenditure for waste disposals. This paper reviews global and local plastic waste generations and current practice of waste disposal methods undertaken by local governments and authorities. The reviews are based on available literature on municipal waste generations in general, and plastic waste generations and disposals in particular, as well as challenges faced by local authorities in dealing with the ever-increasing issues of waste treatment and disposal and the associated economic, social and environmental consequences of plastic waste dilemma. It is found that local authorities are facing increasing challenges in not only to dispose of these plastic wastes in a safe manner but also to look for practical and economic measures to reduce plastic waste generations by its residents. The Federal government, in cooperation with all local governments in the country has embarked on concerted efforts to strengthen its waste planning and management approach towards the next century. However, significant changes in consumer behaviour are detrimental to the success of these efforts to ultimately reduce plastic waste generation in the country.